Pengaruh Pola Rekrutmen dan Disiplin Terhadap Efektivitas Kerja Pegawai di Universitas Muhammadiyah Gorontalo - Umar Sako Baderan (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik (J-EMSPOL), 2024)
This study was conducted with the aim of knowing and analyzing the influence of employee recruitment patterns on employee work effectiveness at the University of Muhammadiyah Gorontalo. The research approach used is Quantitative. The results of this study indicate that: Partially, recruitment patterns have a significant influence on employee work effectiveness. The t-count value obtained is 25,454 while the t-table is obtained with a value of 1,994, this means that the t-count is greater than the t-table. Thus the hypothesis that states that recruitment patterns partially have a significant effect on employee work effectiveness is proven; Partially, discipline has a significant effect on employee work effectiveness. The t-count value obtained is 25,454 while the t-table is obtained with a value of 1,994, this means that the t-count is greater than the t-table. Thus the hypothesis that discipline partially has a significant effect on employee work effectiveness is proven; Simultaneously, Recruitment Patterns and Discipline affect Employee Work Effectiveness. Based on the results of the comparison between Fcount and FTable where Fcount of 366.463 is greater than FTable of 3.12768, it can be interpreted that the Recruitment Pattern and discipline simultaneously or together have a significant effect on the effectiveness of Employee Work at the Muhammadiyah University of Gorontalo